Acute Ischemic Stroke and Acute on Chronic Kidney Disease - Aftab, Raja Ahsan; Hayat Khan, Amer; AbdulRaazaq, Hadeer Akram; Adnan, Azreen Syazril (Nepal Medical Association, 2016)
Ischemic stroke is due to either local thrombus formation or emboli that occlude a cerebral artery, together with chronic kidney disease represent major mortality and morbidity. Here wer present a case of 53 years old Malay man, admitted to a hospital in Malaysia complaining of sudden onset of weakness on right sided upper and lower limb associated with slurred speech. Patient was also suffering from uncontrolled hypertension, hyperlipidemia, chronic kidney disease stage 4, and diabetes mellitus(un controlled). He was diagnosed with acute ischemic stroke with cranial nerve 7 palsy (with right hemiparesis), acute on chronic kidney disease precipitated by dehydration and ACE inhibitor, and hyperkalemia. Patients with ischemic disease and chronic kidney disaese require constant monitering and carefull selected pharmacotherapy. Patient was placed under observation and was prescribed multiple pharamacotherpay to stabalise detoriating condition